Assistance In English Mastery of LKP Aloha Edu (English For Children) Through Game-Based Learning - Wakhid, Lutfi; Ridwan, Ridwan; Ilmi, Rizqi Maulana (Riviera Publishing, 2024)
This community service aims to provide effective and enjoyable learning support to facilitate the acceptance of English language learners into courses and institutions. Today English is an international language that all groups must master. In the world of education, English is introduced from an early age using different methods. In fact, it is not possible to apply effective teaching methods suitable for the level and characteristics of students in all courses. Like LKP Aloha Edu, the teaching and learning process at many elementary levels is still very inefficient, especially in learning English. Inefficiency affects students' motivation and enthusiasm for learning. One reason is the lack of fun learning methods. Therefore, the choice of media must be considered before learning the activity. In this lesson, the community service team used a theoretical approach to English for young learners using a medium suitable for primary school students, namely games, to develop English vocabulary. This media focuses on listening, listening and speaking. The purpose of learning the English language is to increase students' enthusiasm for learning English and to improve their English language skills in a more effective and enjoyable way. The results of this community service are 1. Students' interest and ability to learn English increased. 2. Basic skills, especially in terms of English vocabulary, are more versatile.